Strategi Pencegahan Fraud di Lingkungan Pelabuhan Indonesia - Safuan, Safuan (Owner : Riset dan Jurnal Akuntansi, 2024)
The port is the gateway to a country's economy, so the port must be clean from fraud. The purpose of this study is to determine the strategy developed by Pelabuhan Indonesia to prevent fraud. The method used in this research is qualitative method with a case study approach. The results and conclusions of this study are many studies on fraud prevention in the Indonesian port environment, even though Indonesian ports are one of the entry points for global trade. Therefore, Indonesian ports need an efficient fraud prevention system. The study findings show that Indonesian ports have implemented two fraud prevention strategies. The first strategy is strengthening governance within Pelindo, which includes: a) ratifying GCG guidelines; b) carrying out the signing of an integrity pact; c) gratuity control; d) a violation reporting system called "Pelindo Bersih"; e) socializing the implementation of corporate governance; and f) strengtheningPelindo'ss SMAP. The second strategy involves digitizing services such as Vessel Management System (VMS) and Vessel Traffic Service (VTS), as well as land ones such as Terminal Operating System (TOS), Multipurpose Terminal Operating System (MP-TOS), Car Terminal Operating System (CTOS), Autogate System, Single Truck Identification Data System (STID), Behandle Management System (BMS), and from the customer side such as e-Service developed into i-Hub to minimize national logistics costs, Lower the risk of fraud, and compete on a global scale.